Investigation of the material fragmentation model with the uniform scale subdivision energy distribution - Brodskii, R.E.; Virchenko, Yu.P. (Functional Materials, 2006)
Using the probabilistic Kolmogorov approach for the description of the material fragmentation process, it is shown that in the typical physical situation when the intensity energy inflow in the system is constant the Kolmogorov equation must be temporally inhomogeneous. In this case, for the special model with the uniform scale energy distribution expended for the subdivision, the limit Kolmogorov distribution law for fragment sizes is proved. Используя вероятностный подход А.Н.Колмогорова для описания процесса фрагментации материала, показано, что в типичной физической ситуации, при постоянной интенсивности накачки энергии в систему уравнение Колмогорова должно быть неоднородным по времени. Для этого случая, в специальной модели с равномерным по масштабам распределением энергии, расходуемой на дробление, доказан предельный закон Колмогорова для распределения вероятностей размеров фрагментов. Застосовуючи імовірносний підхід Колмогорова до опису процесу фрагментації матеріалу, показано, що у типовій фізичній ситуації, при постійній інтенсивності накачування енергії до системи рівняння Колмогорова має бути неоднорідним за часом. Для цього випадку, у спеціальній моделі з рівноважним за масштабами розподіленням енергії, що витрачається на дроблення, доведено граничний закон Колмогорова для розподілу імовірностей розмірів фрагментів